Enhanced biological phosphorus removal from wastewater in the tropics - Cokro, Angel Anisa (2018)
Enhanced Biological Phosphorus Removal (EBPR) is a phosphors (P) removal method that utilizes the capacity of Polyphosphate Accumulating Organisms (PAOs) to store P more than what is needed for growth. Conventionally, warm temperatures are thought to adversely affect EBPR, while presence of anaerobic stage with distinct separation of carbon and electron acceptors is considered fundamental for successful EBPR. However, recent findings have challenged these paradigms. This dissertation investigated EBPR at warm temperatures when carbon like volatile fatty acids (VFAs) and electron acceptors (e.g. nitrate and/or nitrite) were concomitantly present. Additionally, this thesis also explored a potential strategy to resuscitate failing EBPR systems at warm temperature via addition of wasted activated sludge (WAS).